PENERAPAN TEKNIK PRIORITY PYRAMID UNTUK MENINGKATKAN AKTIVITAS DAN KEMAMPUAN BERPIKIR KREATIF MATEMATIK PESERTA DIDIK SMP - Eneng Yulianti (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
Background of the research is about the low activity and mathematical creative thinking abilitis for junior high school student in mathematics learning. More students still dominate with their teacher, it made less a visible activity in learning and the student think’s not creative when they solve the problem that their teacher’s given. One of the learning alternative that can be applied for increase their activity are using priority pyramid technique. The purpose of this research is to know the student responses of mathematics, priority pyramid technique, from the achievement and a lot of exercises of match. The method of this research is using Classroom Action Research that which refers to combined step of Sanford and Kemmis. This research was conducted in three cycles. Each of three cycles is about planning, action, observation and reflection. The subject of this research is seventh grade of PGRI 330 Cikancung junior high school with total number of student 27. The research instrument that had been used is observation sheet, formative test, questionnaire and journal. The analyze data technique has been done using circular flow method, such as reduction of data, presentation data and verification. According to analyze is that shows the activity and ability to increase mathematical creative thinking in each cycles after using learning with priority pyramid technique. Besides that, the student’s responses are positive with mathematical learning, priority pyramid technique, from the achievement and a lot exercises of match.